Remotely sensed water color and eutrophication in a downstream lake: Long-term dynamic and driving factors in Hong Lake, China - Xueer Geng; Yadong Zhou; Fan Yang; Baoyin He; Hui Liu; Kai Yu; Qi Feng; Yingying Zhang; Jiefeng Kou; Yun Du (Ecological Indicators, 2025)
Downstream lakes are highly vulnerable to intensified human activities, leading to accelerated water quality deterioration and eutrophication. These lakes are the primary recipients of upstream pollutants, thus requiring urgent monitoring and pollution tracing. This study investigates the long-term (2000–2023) dynamics of water color and eutrophication in Hong Lake, a downstream lake of Four Lakes Watershed (FLW) in China. Water color and trophic state are derived from Landsat imagery using the Forel-UIe method. The spatial–temporal dynamics of water color and eutrophication are analyzed, while the potential driving factors are explored. The results reveal a shift in water color from green to yellow over the past two decades. This change is most pronounced along the northeastern and western shores. Concurrently, the trophic status of Hong Lake transitions from mesotrophic-eutrophic to predominantly eutrophic. Precipitation and wind speed are associated with elevated hue angle of the nearshore regions, while temperature and sunshine hours exert regionally variable effects. Furthermore, intensified land use in the downstream of the FLW contributes to water color deterioration. The increasing percentage of eutrophication in Hong Lake may result from the aquaculture expansion in the watershed. The findings highlight the vulnerability of water quality in the downstream lake and emphasize the urgent need to formulate effective management strategies at the watershed scale to mitigate water quality degradation in Hong Lake and analogous aquatic ecosystems in the downstream region.